BOOK REVIEW OF CEWEK PALING BADUNG DI SEKOLAH by Enid Blyton - Tama, Fuad Widya (LANTERN (Journal on English Language, Culture and Literature), 2013)
BOOK REVIEW OF CEWEK PALING BADUNG DI SEKOLAH by Enid Blyton